A 4-plex Droplet Digital PCR Method for Simultaneous Quantification and Differentiation of Pathogenic and Non-pathogenic Vibrio parahaemolyticus Based on Single Intact Cells - Lei, Shuwen; Gu, Xiaokui; Xue, Wei; Rong, Zhangquan; Wang, Zhe; Chen, Song; Zhong, Qingping (Frontiers in Microbiology, 2020)
Vibrio parahaemolyticus is a significant seafood-borne pathogen, causing serious acute gastrointestinal diseases worldwide. In this study, a reliable 4-plex droplet digital PCR (ddPCR) was successfully developed and evaluated for simultaneous detection of V. parahaemolyticus based on tlh, tdh, ureR and orf8 in food samples using single intact cells. The targets tlh and ureR were labelled with 6-Carboxyfluorescein (FAM), and the targets tdh and orf8 were labelled with 5’-Hexachlorofluorescein (HEX). Due to reasonable proration of primers and probes corresponding into the two fluorescence channels of the ddPCR detecting platforms, the clearly separated 16 (24) clusters based on fluorescence amplitude was obtained. For better results, the sample hot lysis time and the cycle number were optimized. The results showed that 25 min of the sample hot lysis time and 55 cycles exhibited the minimum number of “rain” and maximum fluorescence amplification for precise detection. The sensitivity of this 4-plex ddPCR assay was 39 CFU/mL, which was in accordance with that of time-consuming conventional plate counting and was 10-fold sensitive than that of qPCR. In conclusion, the 4-plex ddPCR assay presented in this paper was a rapid, specific, sensitive and accurate tool for the detection of V. parahaemolyticus including pandemic group strains and could be adopted for differentiation of V. parahaemolyticus in a wide variety of samples.